RELATIONS OF REMOTE WORKING TO MENTAL HEALTH - Nia Sarinastiti; Ario Bimo; Jeffrey Cole (ASPIKOM Jabodetabek Region, 2021)
Since the pandemic, remote work is the only option to keep people’s productivity outside of the workplace. At first, people were happy to not be having to commute, spending more time at home and having extra hours to do interesting activities not related to work. But that did not last long. Approximately six months later indicate changes to mental states. The aim of this research is to understand the relations of remote work during the Covid-19 pandemic to mental health and identify activities that help to bridge mental health issues. Conceptual thinking of the research is based on social networks, social relations, lifestyle preference, social media hashtags. Research method uses social network analytics based on Netlytic.org and Gephi tools to determine the depth of the relations. The result states that remote work has relations to mental health, in which the wellbeing of individuals relates to the way they work, which hence alter the use of time to do other useful activities.